LysM protein BdLM1 of Botryosphaeria dothidea plays an important role in full virulence and inhibits plant immunity by binding chitin and protecting hyphae from hydrolysis - Zhang, He; Wen, Sheng-hui; Li, Pei-hang; Lu, Liu-yi; Yang, Xu; Zhang, Chuan-jie; Guo, Li-yun; Wang, Dongli; Zhu, Xiao-qiong (Frontiers in Plant Science, 2024)
Botryosphaeria dothidea infects hundreds of woody plants and causes a severe economic loss to apple production. In this study, we characterized BdLM1, a protein from B. dothidea that contains one LysM domain. BdLM1 expression was dramatically induced at 6 h post-inoculation in wounded apple fruit, strongly increased at 7 d post-inoculation (dpi), and peaked at 20 dpi in intact shoots. The knockout mutants of BdLM1 had significantly reduced virulence on intact apple shoots (20%), wounded apple shoots (40%), and wounded apple fruit (40%). BdLM1 suppressed programmed cell death caused by the mouse protein BAX through Agrobacterium-mediated transient expression in Nicotiana benthamiana, reduced H2O2 accumulation and callose deposition, downregulated resistance gene expression, and promoted Phytophthora nicotianae infection in N. benthamiana. Moreover, BdLM1 inhibited the active oxygen burst induced by chitin and flg22, bound chitin, and protected fungal hyphae against degradation by hydrolytic enzymes. Taken together, our results indicate that BdLM1 is an essential LysM effector required for the full virulence of B. dothidea and that it inhibits plant immunity. Moreover, BdLM1 could inhibit chitin-triggered plant immunity through a dual role, i.e., binding chitin and protecting fungal hyphae against chitinase hydrolysis.